2011
DOI: 10.1007/s10409-011-0505-1
|View full text |Cite
|
Sign up to set email alerts
|

A spherical cavity expansion model for penetration of ogival-nosed projectiles into concrete targets with shear-dilatancy

Abstract: A dynamic spherical cavity-expansion penetration model is suggested herein to predict the penetration and perforation of concrete targets struck normally by ogivalnosed projectiles. Shear dilatancy as well as compressibility of the material in comminuted region are considered in the paper by introducing a dilatant-kinematic relation. A procedure is first presented to compute the radial stress at the cavity surface and then a numerical method is used to calculate the results of penetration and perforation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…By ignoring the compressibility and strain-softening of concrete, the cavity-expansion pressure would be overestimated; and if shear dilatancy, strain-rate, strain-hardening of concrete are not included, the cavity-expansion pressure would be underestimated. Therefore, under low and medium penetration velocity, the above effects of concrete material generally offset each other, which indicates the incompressible material assumption of target concrete is reasonable [31][32][33]. Additionally, incompressible material assumption excludes the effect of stress wave and thus greatly simplifies the problem with possible analytical solutions.…”
Section: Simplification Of Penetration Problemsmentioning
confidence: 99%
“…By ignoring the compressibility and strain-softening of concrete, the cavity-expansion pressure would be overestimated; and if shear dilatancy, strain-rate, strain-hardening of concrete are not included, the cavity-expansion pressure would be underestimated. Therefore, under low and medium penetration velocity, the above effects of concrete material generally offset each other, which indicates the incompressible material assumption of target concrete is reasonable [31][32][33]. Additionally, incompressible material assumption excludes the effect of stress wave and thus greatly simplifies the problem with possible analytical solutions.…”
Section: Simplification Of Penetration Problemsmentioning
confidence: 99%
“…The authors of [80] compared their model with the model by Forrestal [53] and concluded that the difference between predictions of these two model is negligibly small for impact velocities less than 100 m/s and the discrepancy increases with increase of impact velocities. He et al [81] used similar approach based on quasi-dynamic SCE model.…”
Section: Some Other Models and Related Problemsmentioning
confidence: 99%
“…d 0 is hole diameter, and coefficients a 0 and a 2 are determined by the model of Forrestal et al (1994Forrestal et al ( , 1996. He et al (2011) proposed a spherical cavity expansion penetration model to predict penetration and perforation of concrete shields by ogive-nose projectiles. Shear dilatancy as well as compressibility of material in comminuted region are considered by introducing a dilatant-kinematic relation.…”
Section: Two-stage Modelsmentioning
confidence: 99%
“…The above discussed three-phase model suggested by Teland (2001, 2003) for semiinfinite shields can be modified for shields having a finite thickness. He et al (2011) also suggested using their model not only for semi-infinite shield but also for shields having a finite thickness.…”
Section: Shields Having Finite Thicknessmentioning
confidence: 99%